Habitat productivity and pyrethroid susceptibility status of Aedes aegypti mosquitoes in Dar es Salaam, Tanzania - Leah Mathias; Vito Baraka; Anitha Philbert; Ester Innocent; Filbert Francis; Gamba Nkwengulila; Eliningaya J. Kweka (BMC, 2017)
Abstract Background Aedes aegypti (Diptera: Culicidae) is the main vector of the dengue virus globally. Dengue vector control is mainly based on reducing the vector population through interventions, which target potential breeding sites. However, in Tanzania, little is known about this vector's habitat productivity and insecticide susceptibility status to support evidence-based implementation of control measures. The present study aimed at assessing the productivity and susceptibility status of A. aegypti mosquitoes to pyrethroid-based insecticides in Dar es Salaam, Tanzania. Methods An entomological assessment was conducted between January and July 2015 in six randomly selected wards in Dar es Salaam, Tanzania. Habitat productivity was determined by the number of female adult A. aegypti mosquitoes emerged per square metre. The susceptibility status of adult A. aegypti females after exposure to 0.05% deltamethrin, 0.75% permethrin and 0.05% lambda-cyhalothrin was evaluated using the standard WHO protocols. Mortality rates were recorded after 24 h exposure and the knockdown effect was recorded at the time points of 10, 15, 20, 30, 40, 50 and 60 min to calculate the median knockdown times (KDT50 and KDT95). Results The results suggest that disposed tyres had the highest productivity, while water storage tanks had the lowest productivity among the breeding habitats Of A. aegypti mosquitoes. All sites demonstrated reduced susceptibility to deltamethrin (0.05%) within 24 h post exposure, with mortalities ranging from 86.3 ± 1.9 (mean ± SD) to 96.8 ± 0.9 (mean ± SD). The lowest and highest susceptibilities were recorded in Mikocheni and Sinza wards, respectively. Similarly, all sites demonstrated reduced susceptibility permethrin (0.75%) ranging from 83.1 ± 2.1% (mean ± SD) to 96.2 ± 0.9% (mean ± SD), in Kipawa and Sinza, respectively. Relatively low mortality rates were observed in relation to lambda-cyhalothrin (0.05%) at all sites, ranging from 83.1 ± 0.7 (mean ± SD) to 86.3 ± 1.4 (mean ± SD). The median KDT50 for deltamethrin, permethrin and lambda-cyhalothrin were 24.9-30.3 min, 24.3-34.4 min and 26.7-32.8 min, respectively. The KDT95 were 55.2-90.9 min for deltamethrin, 54.3-94.6 min for permethrin and 64.5-69.2 min for lambda-cyhalothrin. Conclusions The productive habitats for A. aegypti mosquitoes found in Dar es Salaam were water storage containers, discarded tins and tyres. There was a reduced susceptibility of A. aegypti to and emergence of resistance against pyrethroid-based insecticides. The documented differences in the resistance profiles of A. aegypti mosquitoes warrants regular monitoring the pattern concerning resistance against pyrethroid-based insecticides and define dengue vector control strategies.